Ihr Mütter, lasset eure Kinder leben, dass sie euch die Geburt, aber nicht den Tod schulden. - Kandt-Horn, Susanne; Brecht, Bertolt
Quote by Berthold Brecht on the left and on the right section of the painting "Schreckliche Begegnung" by Susanne Kandt-Horn. Suggested translation: Mothers, let your children live, that they owe you the birth but not the death. PO-2189